Diversity and Bioactivity of Endophytes From Angelica sinensis in China - Zhang, Xin-Guo; Guo, Si-Jia; Wang, Wen-Na; Wei, Guo-Xing; Ma, Guo-Yan; Ma, Xiao-Di (Frontiers in Microbiology, 2020)
Plant seeds are not merely reproductive organs, they are also carriers of microorganism, particularly, inherent and non-invasive characteristic endophytes in host plant. Therefore, in this study, the endophytic diversity of Angelica seeds was studied and compared with endophytes isolated from healthy leaves, stems, roots and seeds of A. sinensis using 20 different media. The metabolites of endophytic strains were evaluated with six different methods for their antioxidant activity and the paper disc diffusion method for antimicrobial activities. As a result, 226 endophytes were isolated. Compared with the biodiversity and abundance of uncultured fungi from Angelica seed, the result showed that the most frequent endophytic fungi were Alternaria sp as seen in artificial media; moreover, compared with artificial media, the pathogenic fungi, including Fusarium sp. and Pseudallescheria sp., were not found from the Angelica seed, the results suggested it may not be inherent endophytes in plants. In addition, bacteria from seven phyla were identified by high-throughput sequencing, while five phyla of endophytic bacteria, including Proteobacteria, Actinobacteria, Bacteroidetes, Microgenomates and Saccharibacteria, and were not isolated on artificial media. Furthermore, the sample JH-4 mycelium displayed the best antioxidant activity, and the active constituent may be a flavonoid as determined by total phenol and flavonoid content. Moreover, YH-12-1 mycelium had strong inhibitory activity against the five tested strains and the minimum inhibitory concentration against Pseudomonas aeruginosa and Streptococcus pneumoniae was found to be 25 μg/mL. Our results confirm that plant endophytes are rich in biodiversity and contain important resource of many uncultured microorganisms.